Leisure program planning and delivery - Russell, Ruth V., 1948- (Human Kinetics, 2008)
"Leisure Program Planning and Delivery provides a comprehensive three-step plan for successful programming of leisure services and operational management of program systems in recreation and leisure service organizations. Grounded in contemporary professional practice and real-world applications, the book provides a systematic plan for students to learn the essentials of successful recreation programming, with examples of a variety of activities in community, outdoor, sport, cultural arts, and tourism sectors of the field."--BOOK JACKET.